Interaction of Motives and Submotives in Professional Determination - Jankevičius, Stasys (Acta Paedagogica Vilnensia, 2005)
The essence of motives as wcll as psychological and pedagogical conditions for their training can be bettcr revealed in studying the interaction between the motives and other motivation factors - submotives. Many psychologists in our country and abroad for such motivation factors keep needs, purposes of activities, emotions, wills, habits, the peculiarities of temperament and personality. Interaction of motives and submotives forms complicated hierarchical system of motives, in which an individual motive cannot be changed without affccting all the system. Thercfore, a successful formation of motives in any field of human activities, including the motives of conscious choice of profession, is possible only in the process of complcx and all-round devclopmcnt of pupils personality.